2019
DOI: 10.1016/j.vaccine.2019.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities to improve vaccination coverage in a country with a fledgling health system: Findings from an assessment of missed opportunities for vaccination among health center attendees—Timor Leste, 2016

Abstract: Introduction: Since its independence in 2002, Timor Leste has made significant strides in improving childhood vaccination coverage. However, coverage is still below national targets, and children continue to have missed opportunities for vaccination (MOV), when eligible children have contact with the health system but are not vaccinated. Timor Leste implemented the updated World Health Organization methodology for assessing MOV in 2016. Methods: The MOV data collection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 12 publications
5
18
1
Order By: Relevance
“…Overall, all health workers must be trained on the vaccination schedule and further work may be useful to identify exact gaps in knowledge within the immunization schedule for targeted education. Additionally, although the questionnaire did not test their understanding of catch-up schedules, previous studies show this to be a confusing concept for many health workers and it is necessary to also ensure health workers understand the national policy on catch-up vaccination for children with a delayed schedule [5,29]. As Kenya has continued to add more antigens to their national immunization schedule, with varying target age groups (MCV second dose in 2015, IPV and YF in 2016 and human papillomavirus vaccine in 2019), the potential for MOV has increased and will accelerate further.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Overall, all health workers must be trained on the vaccination schedule and further work may be useful to identify exact gaps in knowledge within the immunization schedule for targeted education. Additionally, although the questionnaire did not test their understanding of catch-up schedules, previous studies show this to be a confusing concept for many health workers and it is necessary to also ensure health workers understand the national policy on catch-up vaccination for children with a delayed schedule [5,29]. As Kenya has continued to add more antigens to their national immunization schedule, with varying target age groups (MCV second dose in 2015, IPV and YF in 2016 and human papillomavirus vaccine in 2019), the potential for MOV has increased and will accelerate further.…”
Section: Plos Onementioning
confidence: 99%
“…As of April 2019, a total of 12 countries across four WHO regions have implemented this methodology [7-9, 27, 28]. Recent studies in Chad, Malawi and Timor Leste using the updated WHO methodology showed that between 41-66% of eligible children had made contact with the health system and were not vaccinated with all the vaccines for which they were eligible [8,29]. In November 2016, to better understand the reasons for under-vaccination and to prioritize needed interventions, the Kenya NVIP conducted a MOV assessment using the updated WHO methodology [28].…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, the Strategic Advisory Group of Experts (SAGE) on immunisation recommended the prioritisation of MOV assessments, based on evidence indicating a global MOV prevalence of 32% [ 31 , 32 ]. While there is currently limited evidence on the magnitude of MOV and the multi-dimensional nature of the factors associated with it, research efforts in this area have increased over the last decade, including in African and other low- and middle-income countries [ 29 , 30 , 33 , 34 , 35 , 36 ].…”
Section: Covid-19 and The Growing Need For Assessing And Addressing Movmentioning
confidence: 99%
“…While there is currently limited evidence on the structural and contextual factors responsible for missed opportunities for vaccination in different contexts, research efforts in this area have increased in recent years. As a result, there has been an increasing body of evidence on the prevalence of missed opportunities for vaccination and associated factors over the last decade, including in African and other low-and middle-income countries contexts [46][47][48][49][50][51]. To date, however, there remain enormous gaps in what is known.…”
Section: Generalmentioning
confidence: 99%